PENGARUH KRISIS MONETER PADA KINERJA KEUANGAN DAN NILAIPERUSAHAAN - Nelli Novyarni (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
This study was aimed analyzing the monetary crisis on financial performance and corporation value effect.This study found that the monetary crisis affect on financial performance and corporation value. The study on 50 manufacturing companies consist of 25 companies variety business and industry and pharmacist notes at Jakarta Stock Exchange from 1992 to 2002 revealed that the monetary crisis cause decrease in financial performance and corporate value. Based on before and after mean financial and Tobin 's Q ratio, it found that the monetary crisis cause decrease in financial performance especially in 1998 and corporation value from 1998 to 2002. This study also found that based on each sector, the monetary crisis affect all financial ratio at sector one, especially in 1998 and 2000 and the monetary crisis just affect debt to equity ratio from to 2002 at sector two. Beside that the monetary crisis affect corporation value of all sectors.Keywords: Monetary crisis; financial ratio; Tobin's Q; Financial Performance; Value of the firm.